Investigation of Charge Waves in the Chromophore of Cation Cyanine Dyes Using 13C NMR Spectroscopy - Ryabitzki, O.B.; Stanova, A.V.; Yashchuk, V.M.; Slominski, Yu.L.; Smirnova, A.L.; Kachkovski, O.D. (Ukrainian Journal of Physics, 2022)
The electron density distribution for a series of symmetric and non-symmetric cation cyanine dyes is investigated on the basis of the data of quantum-chemical calculations and NMR (13С) spectra. It is shown that the calculated atomic charges are in good agreement with the experimental values of chemical shifts. A considerable wave-like alternation of the electron density along the chromophore is found. It is shown that the general electron density distribution represents a superposition of the autolocalized charge and two charge waves generated by the donor finite groups.